Advances in Molecular Characterization and Targeted Therapy in Dermatofibrosarcoma Protuberans. (16th March 2011) - Rutkowski, Piotr; Wozniak, Agnieszka; Switaj, Tomasz
Abstract : The molecular pathogenesis of dermatofibrosarcoma protuberans (DFSP) involves distinctive rearrangement of chromosomes 17 and 22 leading to formation of the COL1A1-PDGFB fusion gene. The knowledge of molecular events underlying development of DFSP resulted in the implementation of targeted therapy with imatinib—a tyrosine kinase inhibitor (TKI), to the clinical practice. The striking efficacy of imatinib in advanced cases of DFSP has been demonstrated in a few clinical trials. Thus, imatinib is currently considered the gold standard in the treatment of inoperable and/or metastatic and/or recurrent cases of DFSP. Therapy with imatinib may potentially facilitate resection or decrease possible disfigurement related to radical surgical procedure. Following partial response on imatinib significant percentage of patients may be rendered free of the disease by surgery of the residual tumor.